PEMBELAJARAN IMPROVISASI DALAM PERMAINAN GITAR ELEKTRIK BERBASIS CAGED SYSTEM DI ISTANA NADA MUSIC SCHOOL - Syaputra, Wahyudi (Jurnal Penelitian Musik, 2020)
The aim of this research is to discover appropriate method in teaching CAGED System applied within an electric guitar improvisation. The methodology of this research is qualitative descriptive research with an approach to the case study. The research was conducted at Istana Nada Music School Jl. Haji Nawi Raya since October 2018 to January 2019. The object of the research is an electric guitar instructor of Istana Nada Music School Development Class focalizing in Development Class. The result of this research shows that the instructor teaches his students with lecture method, demonstration, and drill method. Moreover, the instructor instructs the students to memorize CAGED system patterns on fretboard in order to play the scale, arpeggio and pentatonic also train using another root as well. Applying CAGED System in an improvisation affects the tone colour esulted from the play due to differences strings even in the same pitch although have a little deficiency. The media that have important role in teaching electric guitar improvisation are looper and backing track which are useful in guiding an improvisation. Mastering melody improvisation with triplet rhythm practice reflexes toward chord tone as well as student’s musicality in rhythmic aspect. Last but not least, music references frequently listened may affect the way students improvise their play.